Evolutionary trends in antifungal resistance: a meta-analysis. - Niu, Xueke (2024)
The present paper includes a meta-analysis of literature data on 318 species of fungi belonging to 34 orders in their response to 8 antifungal agents (amphotericin B, caspofungin, fluconazole, itraconazole, ketoconazole, posaconazole, terbinafine, and voriconazole). Main trends of MIC results at the ordinal level were visualized. European Committee on Antimicrobial Susceptibility Testing and Clinical & Laboratory Standards Institute (CLSI) clinical breakpoints were used as the staff gauge to evaluate MIC values ranging from resistance to susceptibility, which were subsequently compared with a phylogenetic tree of the fungal kingdom. Several orders (Hypocreales, Microascales, and Mucorales) invariably showed resistance. Also the basidiomycetous orders Agaricales, Polyporales, Sporidiales, Tremellales, and Trichosporonales showed relatively high degrees of azole multi-resistance, while elsewhere in the fungal kingdom, including orders with numerous pathogenic and opportunistic species, that is, Onygenales, Chaetothyiales, Sordariales, and Malasseziales, in general were susceptible to azoles. In most cases, resistance vs susceptibility was consistently associated with phylogenetic distance, members of the same order showing similar behavior.